Inferring CO2 fertilization effect based on global monitoring land-atmosphere exchange with a theoretical model. (17th July 2020) - Ueyama, Masahito; Ichii, Kazuhito; Kobayashi, Hideki; Kumagai, Tomo'omi; Beringer, Jason; Merbold, Lutz; Euskirchen, Eugénie S; Hirano, Takashi; Marchesini, Luca Belelli; Baldocchi, Dennis; Saitoh, Taku M; Mizoguchi, Yasuko; et al.
Abstract: Rising atmospheric CO2 concentration ([CO2 ]) enhances photosynthesis and reduces transpiration at the leaf, ecosystem, and global scale via the CO2 fertilization effect. The CO2 fertilization effect is among the most important processes for predicting the terrestrial carbon budget and future climate, yet it has been elusive to quantify. For evaluating the CO2 fertilization effect on land photosynthesis and transpiration, we developed a technique that isolated this effect from other confounding effects, such as changes in climate, using a noisy time series of observed land-atmosphere CO2 and water vapor exchange. Here, we evaluate the magnitude of this effect from 2000 to 2014 globally based on constraint optimization of gross primary productivity (GPP) and evapotranspiration in a canopy photosynthesis model over 104 global eddy-covariance stations. We found a consistent increase of GPP (0.138 ± 0.007% ppm −1 ; percentile per rising ppm of [CO2 ]) and a concomitant decrease in transpiration (−0.073% ± 0.006% ppm −1 ) due to rising [CO2 ]. Enhanced GPP from CO2 fertilization after the baseline year 2000 is, on average, 1.2% of global GPP, 12.4 g C m −2 yr −1 or 1.8 Pg C yr −1 at the years from 2001 to 2014. Our result demonstrates that the current increase in [CO2 ] could potentially explain the recent land CO2 sink at the global scale.